2004
DOI: 10.1016/j.jsr.2003.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Farm fatalities to youth 1995–2000: A comparison by age groups

Abstract: Abstract:Although a myriad of research illustrates the safety issues related to farm fatalities in youth populations, very little empirical evidence exists to describe farm fatalities to non-working youth and youth under 16 years of age. Research such as that conducted by Myers and Adekoya (2001) and Castillo et al. (1999) utilize surveillance systems such as the National Traumatic Occupational Fatalities (NTOF) Surveillance System and the Census of Fatal Occupational Injuries (CFOI) to provide information on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 11 publications
1
41
0
Order By: Relevance
“…The National Children's Center for Rural and Agricultural Health and Safety 4 reports that a working or nonworking child dies in an agriculture-related incident every 3 days. Goldcamp and colleagues 5 found that among working youth the annual agricultural fatality rate is 9.3 fatalities per 100,000 youth. Zaloshnja and colleagues 6 report that 26,655 agricultural youth (aged 0-19) are injured and 84 suffer fatal injuries each year; only about 14% of these injuries and fatalities are work related.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The National Children's Center for Rural and Agricultural Health and Safety 4 reports that a working or nonworking child dies in an agriculture-related incident every 3 days. Goldcamp and colleagues 5 found that among working youth the annual agricultural fatality rate is 9.3 fatalities per 100,000 youth. Zaloshnja and colleagues 6 report that 26,655 agricultural youth (aged 0-19) are injured and 84 suffer fatal injuries each year; only about 14% of these injuries and fatalities are work related.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,11 Intervention studies have tested processes to improve the safety of nonimmigrant and immigrant youth agricultural workers. 12−16 Studies have also considered farm parents' beliefs about the safety of their children working on the farm.…”
Section: Introductionmentioning
confidence: 99%
“…The potential risks of agricultural work include being exposed to agricultural machinery, livestock, chemicals, and zoonoses; and having higher potential risks of injuries, reproductive and nervous system damage, and some cancers [Perry, 2003]. Children less than 20 years old incurred an estimated 22,648 agricultural injuries in 2001 [Hendricks et al, 2005] and averaged 116 agriculture fatalities a year between 1995 and 2000 [annualized rate: 9.3 per 100,000 youth, Goldcamp et al, 2004]. …”
Section: Introductionmentioning
confidence: 99%
“…6 In our study majority of the patients were in the age group 21-50 years. Most of the agriculture related injuries are experienced by males.…”
Section: Discussionmentioning
confidence: 60%